Latent classes of energy and nutrient intake and their associations with oxidative stress in rural older adults: a cross-sectional study - Li, Meiman; Kong, Weijuan; Jiang, Ting; Ning, Yanhua (Frontiers in Nutrition, 2025)
BackgroundResearch indicates that diet correlates with oxidative stress; however, the influence of specific energy and nutrient classes has been scarcely studied. This study aimed to investigate the categories of energy and nutrient intake among rural older adults through a latent class analysis and to explore the association between each category and biomarkers of oxidative stress.MethodsIt is a cross-sectional study. Dietary information was obtained from 3 days of 24-h dietary diaries. Levels of oxidative stress markers were measured from fasting venous blood samples. A latent class analysis was used to analyze energy and nutrient intake classes. Analysis of variance and post-hoc comparisons were used to examine the relationships between energy and nutrient classes and oxidative stress.ResultsThis analysis was performed on 376 adults aged 65 years and older. The latent class analysis found that energy and nutrient intake could be divided into three classes: over-adequate nutrition—high energy (n = 141, 37.50% of the total samples), adequate nutrition—low in energy and protein (n = 69, 18.35% of the total samples), and inadequate nutrition (n = 166, 44.15% of the total samples). 8-iso-PGF2α (F = 6.004, p = 0.003) and superoxide dismutase (SOD) (F = 5.559, p = 0.004) are associated with different energy and nutrient latent classes.ConclusionThis study explores how classes of energy and nutrients relate to oxidative stress in rural older adults. The findings provide a basis for future research on oxidative stress and nutrition in the elderly.